Development and acceptability testing of ready-to-use supplementary food made from locally available food ingredients in Bangladesh - Ahmed, Tahmeed; Choudhury, Nuzhat; Hossain, M Iqbal; Tangsuphoom, Nattapol; Islam, M Munirul; de Pee, Saskia; Steiger, Georg; Fuli, Rachel; A M Sarker, Shafiqul; Parveen, Monira; WestJr, Keith P; Christian, Parul (© 2014 BioMed Central Ltd., 2017)
This article was published in BMC Pediatrics [© 2014 BioMed Central Ltd.] and the definite version is available at: http://bmcpediatr.biomedcentral.com/articles/10.1186/1471-2431-14-164